(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Five different brands of locally produced chanachur packets were collected from the market. From each brand, packets of chanachur having the same date of production were bought and stored at ambient condition (30 oC and 60 % RH) for 3 months. The changes in water activity, moisture % and consequent effect on sensory qualities like texture, color, flavor and overall acceptance were investigated every month starting from zero month. Test of packaging materials were also carried out for each brand of packed chanachur. Moisture and water activity values have been increased with time for all the samples (A-E) whereas sensory scores decreased. However, all the chanachur samples except C were found acceptable under the study period. Key words: Chanachur; Water activity; Sensory quality; Packaging materials; Moisture content; Storage condition; Shelf life. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8102 Bangladesh J. Sci. Ind. Res. 46(1), 33-40, 2011